Protocol for a cluster randomised controlled trial on information technology-enabled nutrition intervention among urban adults in Chandigarh (India): SMART eating trial. Issue 1 (1st January 2018) - Kaur, Jasvir; Kaur, Manmeet; Webster, Jacqui; Kumar, Rajesh
ABSTRACT: Nutrition is an important determinant of health. At present, nutrition programs in India mainly emphasize improving maternal and child nutrition. Adult nutrition has not received due attention, though diseases like hypertension and diabetes are largely preventable through changes in dietary and physical activity behaviour. Little is known about the best approaches to improve dietary behaviours, especially the role of modern information technology (IT) in health education. We describe the protocol of the SMART Eating (Small, Measurable and Achievable dietary changes by Reducing fat, sugar and salt consumption and Trying different fruits and vegetables) health promotion intervention. A Cluster Randomised Controlled Trial will evaluate the effect of an IT-enabled intervention on nutrition behaviour among urban adults of Chandigarh, India. Formative research using a qualitative exploratory approach was undertaken to inform the intervention. The IT-enabled intervention programme includes website development, Short Message Service (SMS), e-mail reminders and interactive help by mobile and landline phones. The IT-enabled intervention will be compared to the traditional nutrition education program of distributing pamphlets in the control group. The primary outcome will be the percentage of study participants meeting the dietary intake guidelines of the National Institute of Nutrition, Hyderabad, India and the change in intake of fat, sugar, salt, fruit and vegetables after the intervention. The difference in differences method will be used to determine the net change in dietary intakes resulting from the interventions. Measurements will be made at baseline and at 6 months post-intervention, using a food frequency questionnaire. The formative research led to the development of a comprehensive intervention, focusing on five dietary components and using multi-channel communication approach including the use of IT to target urban North Indians from diverse socio-economic backgrounds. The Cluster Randomised Controlled Trial design is suitable for evaluating the effectiveness of this IT-enabled intervention for dietary behaviour change.